Conceptual Directions of Public Service Quality Improvement in Public Catering Companies - Isaenko, Anatoly Vladimirovich; Korolev, Aleksey Vasilievich (International Review of Management and Marketing, 2016)
The article suggests and substantiates the conceptual directions for improving the quality of public services in public catering companies, which correspond to the problem of eliminating the discrepancies between consumer expectations and perceptions, defined by the content of five-stage model of service quality (The Gap's Model of Service Quality) and typical problems of services: lack or inaccuracy of information on consumers' expectations; lack of service standards provided to consumers; violation of service rules by company's personnel; discrepancy between the declared service quality and real condition. We have suggested a number of managerial decisions aimed at the elimination and minimization of the problems during the provision of public services in public catering companies. According to the completed study we can make a conclusion that for public catering companies the most urgent problem is the twofold development of service standards: procedural and direct communication with consumers. Keywords: public catering company, services quality, conceptual directions, services standards, service personnel. JEL Classifications: L89, M59, M12.